Prostitusi dan Narkoba: Studi Etnografi Pariwisata Kelab Malam di Seminyak - Winawan, I Komang Ayis; Mahagangga, I Gusti Agung Oka; Ariwangsa, I Made Bayu (JURNAL DESTINASI PARIWISATA; Vol 8 No 2 (2020): VOL 8, NO 2 (2020): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2020)
This research aims to provide a description of prostitution and drugs in nightclubs in Seminyak. Honesty, thus research  not to find out who is right or wrong, precisely to emphasize understanding the tourism phenomenon from a different side. The research paradigm is qualitative with ethnographic methods, field research and qualitative techniques. The results showed that sex workers and drug users in Seminyak were not simple problems. Related to the development of the tourism sector, on the one hand, the pursuit of economic growth and the welfare of the community. But on the other hand, it triggers a lot of intrigue and strategies of actors or agent to remain, survive or get stronger in tourism practices in nightclubs. The field research finding controlled abandonment concept have strength evidence that prostitution and drugs exist but are needed according to the agent's interests.   Keywords: drugs, etnography, nigthclubs, prostitution, tourism